Studi Pembuatan Edible Film Gel Okra (Abelmoschus esculentus L.) dengan Penambahan Pati Singkong - Siti Mukaromatul Muslimah; Warkoyo Warkoyo; Sri Winarsih (Universitas Muhammadiyah Malang, 2021)
Edible film is an organic material packaging that has plastic-like properties but is biodegradable. The components of the edible film include hydrocolloids. Okra gel is a long chain hydrocoloid polysaccharide with a high molecular weight and a constituent protein containing both hydrophilic and hydrophobic substances. The hydrophilic characteristics are used to improve the physical properties of solubility. Meanwhile, hydrophobic characteristics are used to improve barrier properties (WVTR). Okra (Abelmoschus esculentus L.) is one of the cultivated plants that is currently underutilized by the community but has benefits and high nutritional content. The addition of cassava starch aims to increase the strength of the edible film. The purpose of this study was to determine the use of okra gel proportion and cassava starch concentration in making edible films which can produce edible film characteristics that meet the standards.This study used a factorial randomized block design (RBD). The first factor is the ratio of okra gel and distilled water (1: 3; 1: 1; 3: 1, 1:0). The second factor is the concentration of cassava starch (2.5% and 5% (w / v)). The parameters tested were yield of raw materials, thickness, solubility, transparency, tensile strength, elongation, WVTR (Water Vapor Transmison Rate) and SEM (Scanning Electron Microscopy).The results showed that there was no interaction between okra gel and cassava starch. However, the comparison of okra gel and distilled water had a significant effect on the transparency value with an average of 0.89-1.60 A546 / mm. The concentration of cassava starch has a significant effect on transparency 0.89-1.60 A546 / mm, tensile strength 0.97-2.33%. Edible film with the best treatment was obtained in G2P1 treatment (ratio of okra gel and distilled water (1: 1) and 2.5% cassava starch) with a thickness of 0.08mm, transparency 0.58A546 / mm, WVTR 3.87g / m2 / 24h, elongation 9.24%, tensile strength 0.74MPa and solubility 23.56%. And SEM analysis results show uneven morphology.